DNA aneuploidy and tissue architecture in oral potentially malignant disorders with epithelial dysplasia assessed by a 10 locus FISH panel - Zaini, Zuraiza Mohamad; Neat, Michael; Stokes, Angela; Tavassoli, Mahvash; Odell, Edward W. (Spandidos Publications, 2020)
Subjectivity in oral dysplasia grading has prompted evaluation of molecular-based tests to predict malignant transformation. Aneuploidy detected by DNA image-based cytometry (ICM) is currently the best predictor but fails to detect certain high risk lesions. A novel multiplex fluorescence in situ hybridization (FISH) panel was used to explore possible explanations by detecting aneuploidy at the single cell level. FISH was compared to reference standard DNA ICM in 19 oral lesions with epithelial dysplasia and used to characterize the cellular architecture. Copy number variation at 3q28, 7p11.2, 8q24.3, 11q13.3 and 20q13.12 and matched chromosome specific loci were assessed by dual-color FISH to assess numerical and spatial patterns of copy number increase and gene amplification. FISH revealed wide variation in copy number at different loci. Only low level copy number gain was present and often in only a small proportion of cells, although usually with all or all but one locus (9/12). Four cases showed gene amplification, one at two loci. Some probes revealed an internal presumed clonal structure within lesions not apparent in routine histological examination. Both methods produced similar diagnostic results with concordance in detection of aneuploidy by both methods in 17 out of 19 samples (89%). We have shown that oral dysplastic lesions may contain very few aneuploid cells at a cellular level, high copy number gain is rare and changes appear to arise from large chromosomal fragment duplications. Single stem lines are relatively homogeneous for loci with copy number gain but there is a subclonal structure revealed by gene amplification in some lesions. © 2020 Spandidos Publications. All rights reserved.